The Counseling on the Impact of Mercury on ASGM Workers in Padesa Village, Lantung District as a Form of Support for the Implementation of RAD-PPM - Nurlaila Agustikawati; Luh Putu Yuliastuti; Dea Lestari; Wahyul Izzah (Pusat Riset dan Inovasi Nasional, 2022)
Gold mining activities in Padesa Village are carried out traditionally, namely with simple and relatively inexpensive techniques using traditional tools and the process of binding gold from the ground using mercury. The mercury residue in the waters of the village of Padesa is 0,002 mg/L anda the average mercury content in yhe waste reservoir is 0,0695 mg/L, which means that is hhas passed the Permenkes Standard No. 32 of 2017. The strategy for implementing mercury-free alternative technology requires very large costs. This causes people to continue to choose to use coils and mercury. The urgency of this community service activity, the low knowledge and awareness of the Padesa Village community about the dangers of mercury and the management of waste water from logs. It is hoped that this service avtivity aims: (1) Increase the knowledge of the Padesa Village community, Lantung Sub-District on the impact of mercury on health and the environment, (2) Encourage the Padesa Village community, Lantung sub-district to change their behavior in managing waste water from logs, (3)Encouraging the community of Padesa Village, Lantung sub-district to take part in controlling environmental pollution caused by mercury waste, (4)Avoiding the negative impact of mercury pollution on health for workers and residents of Padesa Village. The method used is the provision of education to the community through socialization and counseling activities. The result of this activity was that the average target knowledge before being given counseling (Pretest) was 33,89% and increased to 77,22% after being is an increase (Posttest). The impact of this activity is an increase in target knowledge by 43,33% and a change in the behavior of waste water management.